Noninvasive Determination of 2-[(18)F]-Fluoroisonicotinic Acid Hydrazide Pharmacokinetics by Positron Emission Tomography in Mycobacterium tuberculosis-Infected Mice - Weinstein, E. A. (American Society for Microbiology, 2012)
Tuberculosis (TB) is a global pandemic requiring sustained therapy to facilitate curing and to prevent the emergence of drug resistance. There are few adequate tools to evaluate drug dynamics within infected tissues in vivo. In this report, we evaluated a fluorinated analog of isoniazid (INH), 2-[(18)F]fluoroisonicotinic acid hydrazide (2-[(18)F]-INH), as a probe for imaging Mycobacterium tuberculosis-infected mice by dynamic positron emission tomography (PET). We developed a tail vein catheter system to safely deliver drugs to M. tuberculosis aerosol-infected mice inside sealed biocontainment devices. Imaging was rapid and noninvasive, and it could simultaneously visualize multiple tissues. Dynamic PET imaging demonstrated that 2-[(18)F]-INH was extensively distributed and rapidly accumulated at the sites of infection, including necrotic pulmonary TB lesions. Compared to uninfected animals, M. tuberculosis-infected mice had a significantly higher PET signal within the lungs (P < 0.05) despite similar PET activity in the liver (P > 0.85), suggesting that 2-[(18)F]-INH accumulated at the site of the pulmonary infection. Furthermore, our data indicated that similar to INH, 2-[(18)F]-INH required specific activation and accumulated within the bacterium. Pathogen-specific metabolism makes positron-emitting INH analogs attractive candidates for development into imaging probes with the potential to both detect bacteria and yield pharmacokinetic data in situ. Since PET imaging is currently used clinically, this approach could be translated from preclinical studies to use in humans.